2018
DOI: 10.1177/0033354918795888
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants’ Use of eHealth Services in the United States, National Health Interview Survey, 2011-2015

Abstract: Targeted interventions that reduce socioeconomic barriers in accessing technology and promote multilingual electronic portals could help mitigate disparities in use of eHealth services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…In both age groups, survivors with a high school diploma or less were less likely than survivors with more than a high school diploma to use IBHC. Our findings are consistent with older studies that used data from NHIS ( 21 23 ) and studies that used another national population-based survey, the Health Information National Trends Survey (HINTS) ( 8 , 9 , 17 , 18 , 20 , 25 ). In these studies, younger age, being non-Hispanic White, and higher education were generally found to be associated with higher levels of health-related internet use, although the term was more broadly defined, a use of health information technology and health-seeking behaviors, than the term used in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In both age groups, survivors with a high school diploma or less were less likely than survivors with more than a high school diploma to use IBHC. Our findings are consistent with older studies that used data from NHIS ( 21 23 ) and studies that used another national population-based survey, the Health Information National Trends Survey (HINTS) ( 8 , 9 , 17 , 18 , 20 , 25 ). In these studies, younger age, being non-Hispanic White, and higher education were generally found to be associated with higher levels of health-related internet use, although the term was more broadly defined, a use of health information technology and health-seeking behaviors, than the term used in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, earlier studies used a broad definition of health information technology that encompassed activities with and without interactions with health care providers, such as seeking health information online and participating in group chats ( 9 , 17 , 25 ). Other studies evaluated the use of health information technology among the general population or among people with chronic conditions, but not specifically among cancer survivors ( 21 23 ). An updated examination of long-term trends and a focus on IBHC use that includes direct interaction with providers among cancer survivors is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The digital gap does not occur solely due to accessibility to the internet, however, and the reasons for slow adoptability of telehealth by various populations are several and sometimes intertwined as table 1 shows. For instance the CARES clinic treats an immigrant population which has shown to have hurdles to adopting telemedicine [4] that are not always directly linked to internet accessibility. The United States entered the COVID crisis with many factors already contributing to a healthcare divide, and these factors continue to widen this gap during the pandemic.…”
mentioning
confidence: 99%
“…It might be that programs for reducing degree of inequality in access to health services, if are only at the level of national planning, without means for disseminating them to the populations in need of these services, will not succeed. 16,5 Based on such findings it is possible to develop a policy and a plan of intervention at various levels and improve services use in order to promote population health. In addition, in view of the impact of digital divides on services' use among the two populations studied, especially among the Arab population, attention should be given to a better adaptation of online health websites and their accessibility to various population groups.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of sensitivity for minority needs, like for example older Arabs in Israel or immigrants to the US who should be the service consumers, is liable to cause a gap between potential customers and offered services. 4,5 However, it is necessary to examine whether low-level usage of the offered services is due to factors associated purely with cultural perceptions, socio-economic status or to factors related to the services.…”
Section: Introductionmentioning
confidence: 99%